#TITLE_ALTERNATIVE# - Azwin Al Farisi - NIM : 25516006 , Muhamad
The North Coast Reclamation of Jakarta which is intended to be an exclusive area is a debate between those who agree and disagree. The island is planned to be reclaimed as many as 17 islands, namely Island A to Q Island. However, in its development only the Islands C, D and G received approval from the Ministry of Environment and Forestry. With the reclamation of the Island C, D, and G, it is feared that there will be sedimentation because the sediment coming from the river will settle between the C, D and G. Islands. The impact of the reclamation will be silting on the river so that the river water will return to land that causes flooding in the area around the estuary. In addition, sediments will also settle between the cracks of the island which, if allowed, will unite the two islands, namely the C and D islands, which will hamper the shipping lanes in the future. This study aims to determine the sediment rate that occurs, so as to provide an alternative solution to the problems that will be caused by reclamation of the C, D, and G. Islands. The initial stage of the study began with a literature study on related research, then data collection and data processing needed in modeling. The next step is modeling simulation starting from configuration, calibration, and model validation then analyzing and concluding the results of the model. The model uses 0.027 manning roughness values in large areas with a level of tidal average error of 7.57% and in small areas obtained an average error of 2.84%. The modeling results show the sediment will settle in the gap between C and D islands with a height of up to 4 cm per year. Dredging is planned by using the Backhoe dredger SP 1600 type dredger and barge to help transport and dispose of sediment into the sea in accordance with the relevant ministerial regulations.